What do public company audit clients want from their auditor? - Christensen, Brant; Ege, Matthew; Sharp, Nathan; Wilks, T. Jeffrey (Review of Accounting Studies, 2026)
Abstract We survey public company executives and directors to understand what audit clients want from their auditor in today’s regulated environment. Our results provide at least three important takeaways. First, executives and directors view elements of auditors’ service quality (e.g., timeliness of communications) as at least as important as auditors’ technical competence. Second, we find no evidence that stakeholders’ preferences for service quality replaces their expectation for technical competence. Third, we find that 57% of executives and 67% of directors feel they can very accurately assess audit quality after an audit’s completion, but we are unable to identify clear determinants of participants’ self-reported ability to assess quality. Our results highlight the challenges facing auditors as they attempt to please clients, protect shareholders, and comply with regulations, all while offering a product whose quality is inherently challenging for others to assess. Our findings motivate future research and inform regulatory efforts.